A Small-Molecule Cocktails-Based Strategy in Culture of Mesenchymal Stem Cells - Feng, Yuan; Luo, Jing; Cheng, Jintao; Xu, Aimin; Qiu, Dongbo; He, Sixiao; Zheng, Dayong; Jia, Changchang; Zhang, Qi; Lin, Nan (Frontiers in Bioengineering and Biotechnology, 2022)
Mesenchymal stromal cells (MSCs) have a variety of unique properties, such as stem cell multipotency, immune regulation, making them attractive in the field of cell therapy. Before infusion therapy, MSCs are required to undergo tissue separation, purification, and expansion in vitro for a certain period of time. However, in the process of in vitro expansion of MSCs, due to the influence of culture time and culture environment, cell senescence, increased heterogeneity, and function attenuation are likely to occur, which greatly limits their clinical applications. In this study, we use a cocktail of three small molecules compounds ACY (A-83-01, CHIR99021 and Y-27632) to increase the proliferation activity of MSCs in vitro and slow down cell senescence. Moreover, we find that ACY can inhibit the increase in the heterogeneity of MSCs and maintain their differentiation potential. In addition, ACY can maintain the phenotype of MSCs and inhibit the up-regulation of the HLA-DR family of negative markers. In summary, these results suggest that ACY could effectively improve the quantity and quality of MSCs.